Az euróövezet bővítése és euróbevezetési stratégiák - Zsolt Darvas; György Szapáry (Hungarian Academy of Sciences, Institute of Economics, 2008)
– This paper was commissioned by DG ECFIN from the EU Commission as part of the "EMU@10" project and is published in Hungarian language by the permission of the EU Commission. The original English language version of the paper is available at: http://ec.europa.eu/economy_finance/publications/publication_summary12103_en.htm . The paper discusses the risks and challenges faced by the new members on the road to the euro and the strategies for and timing of euro adoption. We investigate the real-nominal convergence nexus from the perspective of euro area entry. We argue that the initial level of economic development as measured by per capita income and the speed of real convergence have a bearing on the strategies to follow and on the timing of entry into euro area. This is because the lower is the per capita income, the larger is the price level gap to close and the greater is the danger of credit booms and overheating. We argue that inflation targeting with floating rates is better suited than hard pegs to manage the price level catching-up process. We suggest a modification in the Maastricht inflation criterion which as currently defined has lost its economic logic.
Keywords: E31; E52; E60; F30; 330; euro area enlargement; convergence; capital flows; credit boom; exchange rate regime; inflation; Maastricht; Eurozone; EU-Mitgliedschaft; Konvergenzkriterien; Wechselkurs; Inflationsrate; EU-Mitgliedschaft